Counterfeited drugs – the economic impact - Sichel, Ricardo Luiz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The problem of counterfeited medicines causes expenditures for the health institutions and public authorities, especially when public health service is concerned. It also causes an expressive loss for the public budget, because of less taxes paid or jobs lost, which has as consequence the payment of welfare money. Moreover, it is also a huge net of illegal activities that finance other forms of illicit activities, such as terrorism, drugs, etc. The paper analyses the economic impact of the trade of illegal products from the perspective of brands which are recognized by consumers and in the context of social interest and problems of public health that are related to the use of inadequate products or medicaments which contained substances that damage the health. It is concluded that the administrative measures that have to be undertaken cannot be limited to the national authorities but should be the result of international cooperation
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 474, s. 203-211
Keywords: counterfeited drugs; medicaments; economic impact; fałszowane leki; produkty lecznicze; wpływ ekonomiczny